Advanced Flame‐Retardant Methods for Polymeric Materials - Liu, Bo‐Wen; Zhao, Hai‐Bo; Wang, Yu‐Zhong (Advanced materials (Weinheim), 2022)
Most organic polymeric materials have high flammability, for which the large amounts of smoke, toxic gases, heat, and melt drips produced during their burning cause immeasurable damages to human life and property every year. Despite some desirable results having been achieved by conventional flame‐retardant methods, their application is encountering more and more difficulties with the ever‐increasing high flame‐retardant requirements such as high flame‐retardant efficiency, great persistence, low release of heat, smoke, and toxic gases, and more importantly not deteriorating or even enhancing the overall properties of polymers. Under such condition, some advanced flame‐retardant methods have been developed in the past years based on “all‐in‐one” intumescence, nanotechnology, in situ reinforcement, intrinsic char formation, plasma treatment, biomimetic coatings, etc., which have provided potential solutions to the dilemma of conventional flame‐retardant methods. This review briefly outlines the development, application, and problems of conventional flame‐retardant methods, including bulk‐additive, bulk‐copolymerization, and surface treatment, and focuses on the raise, development, and potential application of advanced flame‐retardant methods. The future development of flame‐retardant methods is further discussed. Flame‐retardant methods for polymeric materials are reviewed with particular focus on advanced flame‐retardant methods developed in recent years. Both the advantages and drawbacks of these methods are discussed, and prospects for the future development of flame‐retardant methods are presented. It is hoped that this review will guide the development of flame‐retardant polymeric materials.